Case–control study on risk factors for in-hospital mortality in patients with severe COVID-19 - Wu, Kemei; Yin, Lili; Han, Jiangqin; Cai, Qiuhan; Guo, Yang; Jin, Xin; Wu, Jinling; Cheng, Yupei (Frontiers in Public Health, 2024)
Objective The purpose of this study was to identify independent risk factors affecting patient survival and explore predictors of severe cases of coronavirus disease 2019 (COVID-19). Methods We conducted a retrospective, observational, case–control study on adult patients with severe COVID-19 who were admitted to affiliated hospitals in Tianjin between December 18, 2022, and January 31, 2023. We used univariate and multifactorial logistic regression analyses to analyze demographic indicators, comorbidity profiles, and laboratory parameters in two groups of patients (deceased and surviving) to identify independent risk factors for death in patients with severe COVID-19. Results Patients in the deceased group were older than those in the survival group (p = 0.018), and there were more cases of coexisting respiratory insufficiency in the deceased group (p = 0.002). Additionally, laboratory test results for white blood cell count (WBC) and creatine kinase (CK) showed significantly higher values in the deceased group (p = 0.047 and p = 0.029, respectively), while arterial oxygen partial pressure (PAO2) showed significantly lower values compared to the survival group (p = 0.021). Age, respiratory insufficiency, WBCH (highest WBC value), CKH (highest CK value), and PAO2F (first PAO2 value) had area under curve (AUC) values of 0.698, 0.838, 0.721, 0.744, and 0.633, respectively. Conclusion The main risk factors for mortality in patients with severe COVID-19 that we identified in this study were the advanced age of patients, coexisting respiratory insufficiency, elevated levels of WBC and CK, and decreased levels of PAO2. Elevated WBC and CK laboratory parameters, in particular, demonstrated good predictive value for in-hospital mortality risk.